2017
DOI: 10.1108/ijm-12-2015-0205
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of organizational embeddedness on the relationship between quality of work life and turnover

Abstract: Purpose The purpose of this paper is to investigate the mediating effect of organizational embeddedness in the relationship between quality of work life (QWL) and turnover under a foundation of conservation of resources theory. Design/methodology/approach Data were collected from 422 healthcare professionals through a questionnaire survey, and analyzed by means of a confirmatory factor analysis and structural equation modeling. Findings The results indicate that organizational embeddedness has a negative i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 44 publications
(76 reference statements)
1
34
0
Order By: Relevance
“…Employees are likely to increase their embeddedness when they feel connected to their job and their colleagues, feel they fit into the workplace and its culture and have a strong psychological need to protect rather than relinquish resources accumulated through their obligation to the organization. Such resources are supplied from the various contextual forces related to people and their perspectives, for instance perceived organizational support (Halbesleben et al, 2014); quality of work life (Dechawatanapaisal, 2017); work-life balance (Thakur and Bhatnagar, 2017); human resource management practices (Bambacas and Kulik, 2013); locus of control (Ng and Feldman, 2011) and leader-follower relationship (Harris et al, 2011). Resource abundance makes employees become more embedded and obtain positive work outcomes (Halbesleben et al, 2014).…”
Section: Effects Of Lmx Ambivalence On Work Attitudesmentioning
confidence: 99%
“…Employees are likely to increase their embeddedness when they feel connected to their job and their colleagues, feel they fit into the workplace and its culture and have a strong psychological need to protect rather than relinquish resources accumulated through their obligation to the organization. Such resources are supplied from the various contextual forces related to people and their perspectives, for instance perceived organizational support (Halbesleben et al, 2014); quality of work life (Dechawatanapaisal, 2017); work-life balance (Thakur and Bhatnagar, 2017); human resource management practices (Bambacas and Kulik, 2013); locus of control (Ng and Feldman, 2011) and leader-follower relationship (Harris et al, 2011). Resource abundance makes employees become more embedded and obtain positive work outcomes (Halbesleben et al, 2014).…”
Section: Effects Of Lmx Ambivalence On Work Attitudesmentioning
confidence: 99%
“…Additionally, low QWL often reduces the performance of healthcare workers and the quality of care (Grunfeld et al, 2005;Knox & Irving, 1997) and causes high turnover rate (Hayes et al, 2006). Dechawatanapaisal (2017) revealed that perceived QWL, career opportunities, work-life balance and job characteristics were positive and significant predictors of organisational embeddedness. Brooks et al (2007) reported that work design and work content led to a significant increase in workers' desire to stay.…”
Section: Healthcare Workers' Qwlmentioning
confidence: 99%
“…To date, research on job embeddedness has expanded to predict other work outcomes such as organizational citizenship behaviors, innovation-related behaviors, work satisfaction, and performance (Ghosh and Gurunathan, 2015). However, a review of the literature suggests that studies on the antecedents of job embeddedness are still limited (Dechawatanapaisal, 2017; Nguyen et al , 2017; Singh et al , 2018). In particular, it is important to understand embeddedness as an intervening mechanism, including factors that may cause employees to become embedded in an organization (Thakur and Bhatnagar, 2017; Zhang et al , 2012).…”
Section: Introductionmentioning
confidence: 99%